The dog in Kalmyk and Tuvan folklore - Burykin, Aleksey A.; Boldyreva, Indzhir M.; Muzraeva, Delyash N. (The New Research of Tuva, 2019)
The article analyzes folklore materials associated with the dog in the Kalmyk and Tuvan oral traditions. A comparative study of certain cultural elements of the closely related peoples allows, with due regard of common basic elements of community, to complete the general system of representations and concepts that constitute ethnic culture.Due to the special role of the dog in the economy and culture of Kalmyks and Tuvans, the didactic narrative and pragmatics evidently prevail in the bulk of plots and motifs both in the Mongolian (Kalmyks) and Turkic (Tuvans) traditions, despite the observed commonness of other plots and motifs. The paper reveals certain correlations between images of the dog and the wolf. There are multiple stories describing a couple of dogs. ‘Four-eyed’ dogs (with spots above the eyes) are considered sacred. Dogs play a special role in national wedding rites.The research materials include audio recordings of the 1960–1980s stored in the Scientific Archive of the Kalmyk Scientific Center of the Russian Academy of Sciences, as well as published samples of Tuvan fairy tales and epic genres.
Keywords: dog; totemic animal; folklore; rites; wedding rites; signs; healing ability; Kalmyks; Tuvans